Organoid-on-a-chip and body-on-a-chip systems for drug screening and disease modeling. Issue 9 (September 2016) - Skardal, Aleksander; Shupe, Thomas; Atala, Anthony
Highlights: Traditional drug screening model systems are inadequate. Organoid-on-a-chip platforms stand to significantly advance drug and toxicology screening. A wide variety or tissue types have been represented by organoids-on-a-chip. 3D organoid systems better mimic responses of the human body to drug and toxins. Cutting edge multi-organ "body-on-a-chip" systems are currently being developed. Abstract : In recent years, advances in tissue engineering and microfabrication technologies have enabled rapid growth in the areas of in vitro organoid development as well as organoid-on-a-chip platforms. These 3D model systems often are able to mimic human physiology more accurately than traditional 2D cultures and animal models. In this review, we describe the progress that has been made to generate organ-on-a-chip platforms and, more recently, more complex multi-organoid body-on-a-chip platforms and their applications. Importantly, these systems have the potential to dramatically impact biomedical applications in the areas of drug development, drug and toxicology screening, disease modeling, and the emerging area of personalized precision medicine. Teaser: Organoid-on-a-chip and multi-organoid body-on-a-chip platforms stand to significantly advance our capabilities in drug and toxicology screening, disease modeling, and the emerging area of personalized precision medicine.